Seaweeds around the world : state of art and perspectives - Bourgougnon, Nathalie (Advances in botanical research ;, 2020)
Seaweeds around the World: State of Art and Perspectives, Volume 95, includes discussions on current research conducted in the field of algae. Specific chapters cover Isotopic Labeling of Cultured Macroalgae and Isolation of 13C-labeled Cell Wall Polysaccharides for Trophic Investigations, Selected Red Seaweeds from the Philippines with Emerging High-Value Applications, Challenges to the Future Domestication of Seaweed Cultivated Species: Understanding Individual Needs and Physiological Processes for Large-Scale Production, The Importance of Mucilage in Dispersion and Efficiency of Fertilization of Male Gametes, The Application of Seaweeds in Environmental Biotechnology, Indonesian Sargassum Species Prospecting: Potential Applications of Bioactive Compounds, and much more. Presents the most recent biological knowledge and advances on seaweed Content covers innovations to biotechnological, aquacultural and chemical developments about seaweeds field Written by the most experienced authors in the field.